In silico prediction of allergenic hotspots in shrimp tropomyosin applications to the genetic engineering of non-allergenic shrimp varieties and allergenicity assessment of some GM foods - Batongbakal, Sigrid Deytiquez (2004)
This study was designed with the main objective of developing an in silico method of predicting the allergenic hotspots in shrimp tropomyosin and applying the method to the possible production of non-allergenic shrimp varieties, as well as to the allergenicity screening of genetically modified foods. The procedure involved the digestive simulation of the shrimp tropomyosin Pen a 1, simultaneous with the thermostability and aliphatic index determination of the cleaved peptides, followed by the determination of the candidate B cell epitopes, and the identification of the T cell epitopes. The last part entailed the prediction of candidate sequence strings to be used in place of the prredicted B cell and T cell epitopes to produce possible genetically modified (GM) non-allergenic shrimp varieties. The method developed was also applied to screen the potential allergenecity of the recombinant proteins from known GM foods such as the Starlinks corn, Flavr Savr tomato and the antifreeze protein in some fish. The gastrointestinal simulation of Pen a 1 peptide degradation in pepsin pH 1 (stomach) and trypsin (small intestine), produced high molecular weight protease resistant peptide strings (2522 Daltons as maximum value obtained) found to be similar to sequences of the obtained T cell epitopes. The B cell epitope prediction, through the use of the predictive algorithms of Bhaskaran and Ponnuswamy (average flexibility), Janin (average surrounding hydrophobicity), Hopp and Woods (local hydrophilicity) and Kyte and Doolittle (hydropathy) agreed in the ratio of two out of four tests. Of these, the allergenicity hotspot for the allergen Pen a 1 in shrimp was statistically determined to be concentrated in positions 123 to 138, a 16 amino acid length peptide with the sequence SERMRKVLENRSLSDE and in the positions 178 to 194 with the string RAEERAETGESKIVEL. The nearest homologies included the allergens Met e 1, Pan s 1, Cha f 1, Hom a 1, Lep d 10 and Der p 10. The string RVVGNNL which maintained its structure after pepsin and trysin digestion was found to be a T cell epitope binding to HLA DRB1 *0701 allele (at 6% threshold), in DRB*0101 allele (at 5% threshold) and in DRB*0401 allele (at 1% threshold) in the Tepitope program. The peptide string was consistently present in the top 20 binding peptides in the MHCPred and Rankpep predictive tool. Further extending the use of the Tepitope program identifies the DRB*0806 allele, or the DR8 allele in general, most likely to be susceptible to shrimp allergy. The application of the predictive method to screen the possible allergenicity of some genetically modified food proteins yielded candidate B and T cell epitopes rendering the proteins as potentially allergenic. The epitope mapping used in this study has been found to be competent as evidenced by published data on B cell epitope. The digestive simulation results have found correlation with the T cell epitopes, but the aliphatic index still has to establish relativity with any of the epitope mapping methods. Immunological assays are recommended to be done to confirm the data obtained in this computational analysis of the shrimp allergen Pen a 1.